TESTING THE MODEL FOR ENHANCING TEACHER PERFORMANCE USING THE POP-SDM APPROACH WITH LOCAL WISDOM VARIABLES - Rahmawati, Rahmawati; Rubini, Bibin; Novita, Lina (Yayasan Education and Social Center, 2025)
The purpose of this study is to test/validate the teacher performance model using local wisdom variables. The instrument used was a questionnaire for each research variable. The research sample used a multi-stage random sampling technique, selecting 124 teachers in Bekasa Regency who teach at private vocational schools. The data analysis technique used SEM-PLS (Structural Equation Modeling – Partial Least Square). The testing included outer model, inner model, path analysis, coefficient of determination (r2), size effect analysis (f2), predictive relevance analysis (Q2), goodness of fit analysis (GoF), and PLS predict analysis. Based on the tests conducted, it can be concluded that the placement of variables determined by experts is appropriate. These variables are indeed suitable as variables that can increase direct or indirect influence on teacher performance variables.